Misfit dislocation superlattices in IV-VI multilayered compounds as zero-dimensional quantum boxes - Sipatov, A. Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Quantum dots can be generated by a new method based on the formation of misfit dislocations in a perfectly periodic array network during the epitaxial growth of IV-VI compound superlattices. Infrared photoluminescence spectra of IV-VI superlattices are measured at temperatures T=5-90 K. A large blue shift and temperature independent line positions and width were observed in PbSe-PbS/(001)KCl superlattices with a three-dimensional periodic arrays of misfit dislocations. It is supposed that these features are due to quantum dot luminescence.